PANDANGAN HUKUM ISLAM TERHADAP PEMBAGIAN HARTA WARIS KEPADA AHLI WARIS SEBELUM MUWARIS MENINGGAL - Muhammad Jufri; Muhammad Firmansyah (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2021)
Inheritance is the essence of causality (the main cause) in owning property, while property is the bandage of life, both individually and universally. With that treasure the soul of life always revolves. The results show that the practice of distributing inheritance that occurs in the community of Jangkar village, especially in the hamlet of the mosque, is distributed before the muwaris dies. This is done so that when the heirs have died, there will be no quarrels or disputes and enmity, so that between members who are considered heirs still have a good and connected relationship without any problems. According to the view of Islamic law, the distribution of inheritance that occurs in the hamlet community of the Masjid village of Jangkar is not the distribution of inheritance, but in practice it is more directed to grants, because the distribution of assets is given when the muwaris have not died. On the other hand, it is said to be a will, if the heir has the right to own the property given by the muwaris when the muwaris has died. So with regard to the distribution, it can be interpreted that if the distribution is carried out before the muwaris dies, there are two possibilities, namely the distribution is included in the category of grants or wills. And if the distribution is carried out after the muwaris dies, then it also has two possibilities, namely the division of the property is included in the category of wills or inheritance distributions.